The effects of competitiveness on trade balance: The case of Southern Europe - Oscar Bajo Rubio; Burcu Berke; Vicente Esteve García (Kiel Institute for the World Economy (IfW), 2016)
According to the conventional wisdom, "peripheral" Southern European countries members of the euro area (Greece, Italy, Portugal, and Spain) suffer from a problem of competitiveness. Since devaluation is not possible because they are part of the euro, the adjustment should come through decreasing wages and prices in these countries, which, by improving the trade balance, should lead to recover the previous levels of employment and growth. In this paper, the authors estimate trade balance equations for the Southern European countries, both for total trade and for the trade performed with the European Union; and taking three alternative measures of the real exchange rate, i.e., based on consumption price indices, export prices and unit labour costs, respectively. Their main conclusion is that demand seems to be more relevant than relative prices when explaining the evolution of the trade balance.
Keywords: F31; F41; 330; trade balance; real exchange rate; competitiveness